EVOLUTION OF CONODONTS DURING THE LATE CAMBRIAN AND EARLY ORDOVICIAN - Dubinina S.V. (My University, 1998)
Proto-, para-, and euconodonts are characterized, and their stratigraphic significance is evaluated. General evolutionary trends and stages of development are depicted for the Proconodontus, Teridontus, and Hirsutodontus lineages of euconodonts. The potential of using each of the lineages for the terminal Upper Cambrian-Lower Ordovician conodont zonation is outlined for the cold-water, transitional, and warm-water paleo-biogeographic provinces. The Hirsutodontus lineage, whose development commenced since the Late Cambrian (the Batyrbai Age commencement), is established to be independent of the Teridontus lineage. The pre-Trempealeauan interval of the Teridontus lineage development is proved to be characterized by a high evolution rate, and feasibility of using it for elaboration of the lower Upper Cambrian conodont zonation is suggested. It is also demonstrated that evolutionary transitions between euconodont taxa characteristic of the Batyrbai reference section (southern Kazakhstan) delimit the conodont zones of the section and are applicable for detailing the Upper Cambrian-Lower Ordovician conodont zonation in the transitional paleobiogeoraphic province as a whole. The conodont evolution is divided into five stages separated by distinct boundaries. The Cambrian-Ordovician boundary is shown to be marked by principal changes in the conodont evolution.
Keywords: Ordovician; Cambrian; Палеозой::Ордовикская; Paleozoic::Cambrian; Paleozoic::Ordovician; Палеозой::Кембрийская